2017
DOI: 10.1111/eos.12336
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the phosphoinositide 3‐kinase/Akt signaling pathway in bone morphogenetic protein 9‐stimulated osteogenic differentiation and stromal cell‐derived factor 1 production in human periodontal ligament fibroblasts

Abstract: Recent studies have shown that bone morphogenetic protein 9 (BMP-9) can induce osteogenic differentiation in human periodontal stem cells and human periodontal ligament fibroblasts (PDLFs). Bone morphogenetic protein 9 may be used in periodontal tissue regeneration because of its potent osteoinductive ability. Human periodontal ligament cells also have been demonstrated to produce stromal cell-derived factor 1 (SDF-1), which is important for stem-cell homing and recruitment to injured sites. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Our analysis showed that TGF-β, Notch, MAPK, and Ras signaling pathways mediate BMP9-induced differentiation. This result corroborates previous findings identifying the mechanism of BMP9-induced osteogenic differentiation [14,27,65,66,67,68]. Simultaneously, our results also revealed that insulin, PPAR, glutathione metabothyroid hormone, TNF, PI3K-Akt, and several cancer pathways are also involved in BMP9-mediated cellular differentiation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our analysis showed that TGF-β, Notch, MAPK, and Ras signaling pathways mediate BMP9-induced differentiation. This result corroborates previous findings identifying the mechanism of BMP9-induced osteogenic differentiation [14,27,65,66,67,68]. Simultaneously, our results also revealed that insulin, PPAR, glutathione metabothyroid hormone, TNF, PI3K-Akt, and several cancer pathways are also involved in BMP9-mediated cellular differentiation.…”
Section: Resultssupporting
confidence: 93%
“…Several recent studies demonstrated that Notch signaling is required for BMP9-regulated bone formation in MSCs [14,27,48,64]. However, some studies also demonstrated that BMP9 can induce MSCs to differentiate into various cell types [22,65,66]. Moreover, aberrant BMP9 expression might be involved in certain diseases [20,29,34].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, a role for SDF1/CXCR4 signaling in macrophage attraction has been described before in rodent models of breast cancer and tumor relapse after chemotherapy ( Hughes et al, 2015 ; Boimel et al, 2012 ). Our data show that the pre-neoplastic AKT1 cells produce Sdf1b, which is in line with previous studies showing that AKT1 is involved in activating the expression of SDF1 ( Furue et al, 2017 ; Conley-LaComb et al, 2013 ). Other studies revealed an AKT-mediated induction of the transcription factor specificity protein 1 (Sp1) and Sp1-binding sites were shown to be functional within the human SDF1 promoter ( Gómez-Villafuertes et al, 2015 ; Pore et al, 2004 ; García-Moruja et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…Because of the heterogeneity of PDLCs, there is contradictory evidence about whether PDLCs have the capacity to differentiate into osteoblast or form hard tissue following osteogenic induction. Many researchers reported that PDLCs had the ability to differentiate into osteoblast-like cells when triggered appropriately (Fuchigami et al, 2016; Seubbuk et al, 2017; Furue et al, 2017). However, the osteo-inductive methods were highly variable and certain experimental perturbations existed which might impair the validity of the results (Hu et al, 2014; An et al, 2015; Seubbuk et al, 2017; Wei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%